Pragmatic Study "Iraqi EFL Learners' Performance in Adverbial Movements" - غانم، حقي إسماعيل (جامعة بغداد - كلية التربية ابن رشد, 2019)
The study deals with adverbial movements as one of the common methods in the origin of the English language on the one hand, and because it is problematic for learners of English language on the other hand. The study assumes that Iraqi learners face difficulties in using these adverbial. Their performance at the cognitive level is better than the productive level. The hypotheses were varied through the adoption of a diagnostic approach to ten questions. The research was carried out on a sample of 190 students from the English language learners. Where the answers to the topics were collected and analyzed to extract the results of the study: The results indicated that students do not have difficulty in using English. and the subjects’ responses have been collected and analyzed in order to draw the findings of this study. - These results indicate that the students don't face difficulty in using in English which, in turn, confirm the hypothesis of the study. - There are main differences between males and females in the ability to understand the adverbial movement, and the differences in favor of females.
تهتم هذه الدراسة بتحريك الظروف باعتبارها أحد الطرق الشائعة في أصل اللغة الإنكليزية من جهة، ولكونها تشكل إشكالية لمتعلمي اللغة الإنكليزية من جهة أخرى. وتفترض الدراسة: -أن المتعلمين العراقيين يواجهون صعوبات في استعمال هذه الظروف نتيجة عوامل متعددة. -أداءهم في المستوى الإدراكي أفضل من المستوى الإنتاجي. وتنوعت هذه الفرضيات من خلال تبني تصور تشخيصي لعشرة أسئلة، حيث طبق البحث على عينة مؤلفة من (190) طالب من متعلمي اللغة الإنكليزية. حيث جمعت إجابات المواضيع وحللت لاستخراج نتائج الدراسة: وأشارت النتائج إلى أن الطلبة لا يواجهون صعوبة في استعمال اللغة الإنكليزية.
Keywords: صعوبات التعلم -- تعلم اللغة الإنجليزية -- اللغة الإنجليزية كلغة أجنبية